2007
DOI: 10.1080/09286580600943598
|View full text |Cite
|
Sign up to set email alerts
|

Current Indications and Resultant Complications of Evisceration

Abstract: Blind painful eye, endophthalmitis, phthisis bulbi, severe traumatic injury, and glaucoma were the major indications for eviscerations in a tertiary eye care center.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
5
4

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 22 publications
1
28
5
4
Order By: Relevance
“…This is similar to the findings of previous authors who have reported these as major indications for evisceration1617 in patients who sought relief and improved cosmesis.…”
Section: Discussionsupporting
confidence: 92%
“…This is similar to the findings of previous authors who have reported these as major indications for evisceration1617 in patients who sought relief and improved cosmesis.…”
Section: Discussionsupporting
confidence: 92%
“…As principais etiologias que desencadearam a retirada do globo ocular foram trauma ocular, glaucoma, melanoma de coróide e phthisis bulbi. Não obstante, este resultado foi semelhante ao encontrado em outros estudos (10,12,14,15) ; embora a endoftalmite, em alguns destes estudos, tenha se destacado dentre as principais complicações, fato não sucedido neste trabalho.…”
Section: Discussionunclassified
“…Múltiplos estudos descrevem a predominância do gênero masculino no trauma ocular (10,15,21) . Em um estudo na Suécia foram apurados 927 ferimentos oculares demonstrando presença do sexo masculino em 86% dos casos (22) , assim como em uma amostra de 2032 pacientes, um estudo na Irlanda do Norte revelou que 1707 das injúrias oculares (84%) ocorreram em homens (23) .…”
Section: Discussionunclassified
See 2 more Smart Citations